Environmental psychology : an introduction - Steg, Linda; Berg, Agnes E. van den; de Groot, Judith I. M. (Chichester, West Sussex : BPS Blackwell, 2012)
'Explores the environment's effects on human wellbeing and behaviour, factors influencing environmental behaviour and ways of encouraging pro-environmental action'--
Includes index.
Keywords: Environmental psychology